ОПРЕДЕЛЕНИЕ ВЕРОЯТНОСТНЫХ СВОЙСТВ ЭЛЕКТРИЧЕСКИХ ХАРАКТЕРИСТИК ЦЕПЕЙ ЭЛЕКТРОРАЗРЯДНЫХ УСТАНОВОК С УЧЕТОМ СТОХАСТИЧЕСКИ ИЗМЕНЯЮЩИХСЯ ИХ ПАРАМЕТРОВ - Щерба, А.А.; Супруновская , Н.И.; Иващенко, Д.С. (Інститут електродинаміки НАН України, Київ, 2019)
An approach to determination of probabilistic properties (probability density function, the probability distribution function, expectation) of electrical characteristics of charge circuits of reservoir capacitors of electric installations whose active resistance can vary randomly is proposed. It is assumed that resistance is characterized by a continuous random variable whose probabilistic properties are known. As examples, the probabilistic properties of capacitor voltage and choke voltage in the circuits of the first and second order with a stochastically changing active resistance having a normal or uniform probability distribution were studied. References 14, figures 3.